OVERVIEW OF PREGNANT WOMEN'S KNOWLEDGE ABOUT PREPARATION SIBLING RIVALRY IN PUSKESMAS WORK AREA PAKANDANGAN DISTRICT PADANG PARIAMAN - Aulia Asman; An Autika Asman (JOURNAL SCIENTIFIC OF MANDALIKA (JSM), 2021)
The root of sibling rivalry is jealousy between children in the same family. Jealousy was first seen when the older brother had a new sibling. This happens to all parents/pregnant women who have two or more children. As a result of being jealous of a brother towards his sister, the older brother can be aggressive, such as pulling his sister from the swing or bed, hitting and strangling the younger brother. Based on the results of interviews, 3 out of 5 pregnant women said they did not know what sibling rivalry was and how to prepare for sibling rivalry. The purpose of this study was to describe the knowledge of pregnant women about the preparation of sibling rivalry in the work area of ​​the Feeddangan Public Health Center, Padang Pariaman Regency. Sibling rivalry is jealousy of a brother or sister and can cause envy among them which can cause frustration and stress in the first child (Anggraini, 2010). The benefit of sibling rivalry is to teach children to overcome differences, one way is to control children so they don't act aggressively. The factors that cause sibling rivalry are competence and emotional characteristics such as being easily bored, easily frustrated and easily angry. Preparation for sibling rivalry is by preparing older siblings before the presence of their younger siblings. The impact of sibling rivalry is that it will cause negative behavior such as disrespecting others and being happy to see siblings in trouble. This research uses descriptive method. The population in this study amounted to 98 people and a sample of 30 people was taken by accidental sampling. Then after the questionnaires are collected, they are processed manually and presented in a frequency distribution table. The results showed that, respondents' knowledge about the meaning of sibling rivalry was high (93%), the benefits of sibling rivalry were low (57%), the factors causing high sibling rivalry (67%), preparation for overcoming sibling rivalry were low (57%), and the impact of sibling rivalry. high rivalry (87%). The number of respondents whose knowledge level is very low, such as the benefits and preparation for overcoming sibling rivalry, needs to be paid attention to by health workers at the Puskesmas and the Health Office, through counseling and information (newspapers, tv, radio).